A framework for transformational leadership to enhance teacher’s work performance - Yu, Xia; Jang, Guanwei (Frontiers in Psychology, 2024)
This research focused on identifying the behavioral characteristics of transformational leaders in private universities in China and the impact on teachers' work performance and explored the ways to improve teachers' performance in private universities. The researcher wanted to know whether the leaders in China's Private universities display transformational leadership. Did transformational leadership and transformational leaders' organizational vision, inspiring communication, intellectual stimulation, supportive leadership, personal recognition, and moral modeling have an impact on teachers' work performance? This study utilized an input-process-output approach. Face-to-face interviews were conducted with 12 leaders of Guangdong University of Science and Technology (GDUST) to provide qualitative data; and 392 university teachers were surveyed with an electronic questionnaire, which provided data for the quantitative study. SPSS26.0, AMOS24.0 and NVIVO14 were used to organize and analyze the data. After exploratory factor analysis, confirmatory factor analysis, common method bias and correlation analysis. Then, used AMOS24.0 to build the structural equation model, two alternative models were measured to explain the relationship between transformational leadership and teachers' work performance, and to examine the effect of each dimension of transformational leadership on teachers' work performance. The study's results revealed that leaders are implementing transformational leadership styles in private universities in China, but to a lesser extent and teachers' work performance scores are not also high. Transformational leadership has a positive impact on the performance of university faculty. Among them, organizational vision, intellectual stimulation, and personal recognition had a positive impact on teachers' work performance. However, supportive leadership inspiring communication and moral modeling were not confirmed in Chinese private universities. Based on the findings, a framework for enhancing teachers' work performance from a transformational leadership perspective was output. This study contributed to private universities in achieving various goals and promoting sustainability while enriching the theory of transformational leadership.